Efficacious engineering on charge extraction for realizing highly efficient perovskite solar cells. Issue 12 (21st November 2017) - Yue, Shizhong; Liu, Kong; Xu, Rui; Li, Meicheng; Azam, Muhammad; Ren, Kuankuan; Liu, Jun; Sun, Yang; Wang, Zhijie; Cao, Dawei; Yan, Xiaohong; Qu, Shengchun; et al.
Abstract : A systematic strategy for effectively engineering the charge extraction in inverted structured perovskite solar cells based on CH3 NH3 PbI3− x Cl x is provided. An optimized power conversion efficiency of 20.5% is realized. Abstract : Efficient extraction of photogenerated charge carriers is of significance for acquiring a high efficiency for perovskite solar cells. In this paper, a systematic strategy for effectively engineering the charge extraction in inverted structured perovskite solar cells based on methylammonium lead halide perovskite (CH3 NH3 PbI3− x Cl x ) is presented. Intentionally doping the chlorine element into the perovskite structure is helpful for obtaining a high open circuit voltage. The engineering is carried out by modifying the aluminium cathode with zirconium acetylacetonate, doping the hole transport layer of nickel oxide (NiO x ) with copper and using an advanced fluorine doped tin oxide (FTO) substrate. This improves the bandgap alignment of the whole device, and thus, is of great benefit for extracting the charge carriers by promoting the transport rate and reducing the trap states. Consequently, an optimized power conversion efficiency of 20.5% is realized. Insights into how to extract charge carriers efficiently with a minimum energy loss are discussed.